Implementation of critical pathway for dying patients and their families - Nakao, Masatoshi; Tanaka, Kuniko; Hori, Natsuki; Takayama, Akiko (The Journal of Japan Society for Health Care Management, 2007)
In order to examine the usefulness of the critical pathway as a medical standardization relief tool, critical pathway concerning the nursing care of patients who had died during the one year period of April 2005 to March2006was examined. Of the total number of patients who had died during that period, 115patients (60%) were applied to this research. A 1st step was to define a goal of “the ability to satisfactorily prepare for the care of the dying”. Then within the first day, care of the patient was individually set. This was followed by defining a second goal of “aiming by staying calm for a life end with as little pain as possible”. The critical pathway application period for 3 days or less was over 60%, and for8days and more it was still over10%. Some of the outcomes were that the starting point of standardization is the staff's consciousness towards the care, towards the care content and towards the standardization method, and another one was that expenditure of the flat rate system ward as well as early reception and abnormal (unhealthy) grief of a death in a family decreased. Even though overall satisfaction was good in all cases, issues concerning the evaluation of families need to be examined further in the future. In regard to the structure of the critical pathway itself, non application cases, assessment of critical path and examination of those death cases where only records exist and establishment of a care method of the preparation time before the actual care are problematic points and application standards for the critical pathway need to be researched further.